2014
DOI: 10.3389/fphar.2014.00146
|View full text |Cite
|
Sign up to set email alerts
|

Successful therapies for Alzheimer’s disease: why so many in animal models and none in humans?

Abstract: Peering into the field of Alzheimer’s disease (AD), the outsider realizes that many of the therapeutic strategies tested (in animal models) have been successful. One also may notice that there is a deficit in translational research, i.e., to take a successful drug in mice and translate it to the patient. Efforts are still focused on novel projects to expand the therapeutic arsenal to “cure mice.” Scientific reasons behind so many successful strategies are not obvious. This article aims to review the current ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
114
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(120 citation statements)
references
References 114 publications
2
114
0
1
Order By: Relevance
“…Although mild impairment of proteostasis extends lifespan in Caenorhabditis elegans, referred to as hormesis, sustained impairment is accompanied by loss of PQC to neutralize this effect 3,5 . Importantly, evidence indicates that the amount of soluble, aggregate prone protein oligomers, rather than the abundance of pro tein aggregates, correlates with disease severity 23,24 . Therefore, protein aggregates, which contain both misfolded proteins and elevated levels of chaper ones, constitute an adequate PQC response, aimed at sequestering potentially harmful protein oligomers, rather than embodying the ultimate cellular threat 25 .…”
mentioning
confidence: 99%
“…Although mild impairment of proteostasis extends lifespan in Caenorhabditis elegans, referred to as hormesis, sustained impairment is accompanied by loss of PQC to neutralize this effect 3,5 . Importantly, evidence indicates that the amount of soluble, aggregate prone protein oligomers, rather than the abundance of pro tein aggregates, correlates with disease severity 23,24 . Therefore, protein aggregates, which contain both misfolded proteins and elevated levels of chaper ones, constitute an adequate PQC response, aimed at sequestering potentially harmful protein oligomers, rather than embodying the ultimate cellular threat 25 .…”
mentioning
confidence: 99%
“…104 Early on, the discovery that neurodegenerative diseases such as AD were invariably accompanied by the accumulation of amyloid aggregates or plaques prompted the conclusion that the aggregates themselves were toxic but, as murine models of the disease were developed in the recent past, a more nuanced view has emerged. 105 As noted above, amyloidosis in the cardiac system is well-characterized, with multiple proteins such as transthyretin, the immunoglobulin light and heavy chains, serum amyloid A, atrial natriuretic factor and a subset of the apolipoproteins confirmed as being amyloidogenic in the heart. 106 However, the study of other cardiac diseases that are characterized by the intracellular deposition of proteinaceous aggregates has been instructive as well in determining the pathogenic sequelae associated with abnormal peptide aggregates in the cardiomyocyte.…”
Section: Mechanistic Basis For Protein Aggregation Toxicitymentioning
confidence: 96%
“…5 The goal of such a model is to replicate the salient disease features at the expense of the extraneous ones. For example, modeling flight would entail defying gravity, but without the need for building a machine with beaks or feathers.…”
Section: Why So Many Drugs Have Failedmentioning
confidence: 99%